Development of the Politala Internal Quality Audit Information System - Noor, Agustian; Hafizd, Khairul Anwar; Herpendi (Cattleya Darmaya Fortuna, 2023)
This research aims to develop an Internal Quality Audit Information System (SI AMI) at Politala. The problem currently encountered is that the AMI audit process is carried out by filling out a form with Microsoft Office Word and then printing it to be submitted to the Auditor team. This form must be accompanied by physical documents which will be examined by the Auditor. When the audit process is complete, the auditor is obliged to write an Audit Minutes to be signed together. However, this event report was written in Microsoft Office Word and then printed. This is certainly risky in terms of data storage and effectiveness and efficiency in P4MP administrative governance. The system built was designed with Flowcharts, ERD and DFD and was built with the CodeIgniter Framework and SQL Server as the database. The system development method uses the Prototype model and testing uses Blackbox Testing. SI AMI was successfully built and tested showing the results of each function running well (successfully). With the system built (SI AMI) the audit process becomes more effective and efficient because the data is taken automatically and integrated between users, making the data synchronous